The Lateral Preoptic Area: A Novel Regulator of Reward Seeking and Neuronal Activity in the Ventral Tegmental Area - Gordon-Fennell, Adam G.; Will, Ryan G.; Ramachandra, Vorani; Gordon-Fennell, Lydia; Dominguez, Juan M.; Zahm, Daniel S.; Marinelli, Michela (Frontiers in Neuroscience, 2020)
The lateral preoptic area (LPO) is a hypothalamic region whose function has been largely unexplored. Its direct and indirect projections to the ventral tegmental area (VTA) suggest that the LPO could modulate the activity of the VTA and the reward-related behaviors that the VTA underlies. We examined the role of the LPO on reward taking and seeking using operant self-administration of cocaine or sucrose. Rats were trained to self-administer cocaine or sucrose and then subjected to extinction, whereby responding was no longer reinforced. We tested if stimulating the LPO pharmacologically with bicuculline or chemogenetically with Designer Receptors Exclusively Activated by Designer Drugs (DREADDs) modifies self-administration and/or seeking. In another set of experiments, we tested if manipulating the LPO influences cocaine self-administration during and after punishment. To examine the functional connectivity between the LPO and VTA, we used in vivo electrophysiology recordings in anesthetized rats. We tested if stimulating the LPO modifies the activity of GABA and dopamine neurons of the VTA. We found that stimulating the LPO reinstated cocaine and sucrose seeking behavior but had no effect on reward intake. Furthermore, both stimulating and inhibiting the LPO prevented the sustained reduction in cocaine intake seen after punishment. Finally, stimulating the LPO inhibited the activity of VTA GABA neurons while enhancing that of VTA dopamine neurons. These findings indicate that the LPO has the capacity to drive reward seeking, modulate sustained reductions in self-administration following punishment, and regulate the activity of VTA neurons. Taken together, these findings implicate the LPO as a previously overlooked member of the reward circuit.